Effects of pericardiectomy on training- and myocardial infarction-induced left ventricular hypertrophy, chamber dimensions and gene expression - Wolff, A. M.; Rasmussen, T. P.; Wichern, C. R.; Peterson, M. R.; Stayton, M. M.; Thomas, D. P. (International Journal of Sports Medicine, 2017)
The primary purpose of the study was to evaluate whether a pericardiectomy (PERI) alters training- or myocardial infarction (MI)-induced left ventricular hypertrophy (LVH), chamber geometry, gene expression and/or running performance. Mice were randomized into 6 groups: naïve control (CONT)-sedentary (Sed), CONT-trained (Tr), PERI-Sed, PERI-Tr, MI-Sed and MI-Tr. MI mice also received a pericardiectomy as part of the MI surgical procedure. 10 weeks of treadmill running resulted in enhanced running performance-to-exhaustion in all 3 trained groups (CONT-Tr, PERI-Tr, MI-Tr) compared to sedentary cohorts (P<0.001). Training also resulted in similar increases in normalized LVH (LV/BW) in CONT-Tr and PERI-Tr mice. 2D-echocardiographic evaluation of LV internal chamber dimensions revealed that stroke diameter (SD) was larger in PERI compared to MI (P<0.01) but not CONT mice. Ventricular B-type natriuretic peptide mRNA (BNP) was elevated only in the 2 MI groups. Left ventricle β1-adrenergic receptor (β1-AR) and melusin transcripts both demonstrated an overall increase in trained compared to sedentary mice (both P<0.05). Additionally long-term pericardiectomy did not further enhance running performance or increase LV/BW in either sedentary or trained mice.
Keywords: infarction; left ventricular dilation; melusin; pericardiectomy; training